Rate of force development and muscle activation of trunk muscles in women with and without low back pain: A case-control study - Rossi, Denise Martineli; Morcelli, Mary Hellen [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Denadai, Benedito Sergio [UNESP]; Goncalves, Mauro [UNESP]; Navega, Marcelo Tavella [UNESP] (Churchill Livingstone, 2017)
Objective: To evaluate the rate of force development (RFD) and the rate of electromyography rise (RER) of global and local trunk muscles in women with and without low back pain. Design: Cross-sectional study. Setting: Laboratory setting. Participants: Twenty-eight women divided into low back pain (LBP, n = 14) and control groups (CG, n = 14) participated in this study. Main outcome measures: Subjects performed isometric contractions of trunk using an isokinetic dynamometer, and simultaneously the electromyography (EMG) signals were collected for global (rectus abdominis and longissimus thoracic) and local (internal oblique and multifidus) muscles. All variables were calculated using Matlab software. Results: Symptomatic subjects showed lower RFD during trunk extension and it was correlated to a reduced RER mainly in the trunk extensor musculature (p < 0.05). During trunk flexion, LBP exhibited a delayed time to reach peak RFD (p < 0.05) compared to CG. RER for global anterior muscle was higher than for local muscle (p < 0.05) and it was more persistent in asymptomatic women. CG also presented greater activation amplitude for both agonist and antagonist trunk muscles, mainly the global ones. Conclusion: Symptomatic women showed lower RFD and it was correlated to a reduced capacity of rapid muscle activation mainly in the trunk extensor musculature. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Muscle strength dynamometer; Abdominal muscles; Electromyography; Low back pain